2019
DOI: 10.13181/mji.v28i1.2863
|View full text |Cite
|
Sign up to set email alerts
|

CD133, CD44, and ALDH1A1 as cancer stem cell markers and prognostic factors in epithelial ovarian cancer

Abstract: BACKGROUND Ovarian cancer is a heterogeneous disease, and most patients are diagnosed at an advanced stage. Epithelial ovarian cancer type II is characterized by rapid tumor growth and is genetically more labile than type I. This study was aimed to demonstrate the prognostic value of CSC by using the markers CD133, CD44, and ALDH1A1 in EOC.METHODS Clinicopathological and demographic data were collected from medical records. The markers CD133, CD44, and ALDH1A1 were examined with flow cytometry and immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Among 34 malignant tumors in our study, 22 (64.7%) were high grade and 12 (35.3%) low grade. Pelupessy et al 29 found similar findings in their study, that is, 56.7% high grade and 43.3% low-grade tumors.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Among 34 malignant tumors in our study, 22 (64.7%) were high grade and 12 (35.3%) low grade. Pelupessy et al 29 found similar findings in their study, that is, 56.7% high grade and 43.3% low-grade tumors.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have suggested that CD44 overexpression promotes cells migration and metastasis for human solid tumors, including breast carcinoma and ovarian carcinoma. 29,32 The expression pattern of CD44 in malignant cells is of great importance, since CD44 is the main receptor for hyaluronan, and the hyaluronan binding domain exists in all CD44 isoforms and CD44-HA interaction involved in tumor progression. Hence, much effort has focused in blocking the CD44-HA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although contradictory evidence is still available, there is a link between CD133 expression status in ovarian cancer and several other clinicopathological factors. A recently published study by Pelupessy et al, (2019) showed that CD133-negative expression in ovarian cancer correlates with a higher chemoresistance score and has a better ROC curve. In comparison, increased CD133 expression was observed during OCSC induction and chemotherapy drug treatment (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Angka harapan hidup selama 5 tahun pada stadium I karsinoma ovarium lebih dari 90%, sedang pada stadium III/IV mempunyai angka harapan hidup 5 tahun sekitar 30%. 13 Data histopatologik Badan Registrasi Kanker Indonesia tahun 2009 menyatakan kanker ini menempati urutan kelima dari seluruh keganasan pada wanita setelah organ payudara dan leher rahim. 14 Karsinoma ovarium tipe serous merupakan tipe karsinoma ovarium yang paling sering, sekitar lebih dari 50% dari karsinoma ovarium .10 Penelitian yang dilakukan Rojas et al menunjukkan bahwa karsinoma ovarium tipe serous merupakan tipe paling banyak dijumpai mencakup 68%-71%.…”
Section: Diskusiunclassified